2019
DOI: 10.3892/or.2019.7293
|View full text |Cite
|
Sign up to set email alerts
|

Co‑culturing with hypoxia pre‑conditioned mesenchymal stem cells as a new strategy for the prevention of irradiation‑induced fibroblast‑to‑myofibroblast transition

Abstract: Cardiac fibrosis is a pathological consequence of radiation-induced fibroblast proliferation and fibroblast-to-myofibroblast transition (FMT). Mesenchymal stem cell (MSC) transplantation has been revealed to be an effective treatment strategy to inhibit cardiac fibrosis. We identified a novel MSC-driven mechanism that inhibited cardiac fibrosis, via the regulation of multiple fibrogenic pathways. Hypoxia pre-conditioned MSCs (MSCsHypoxia) were co-cultured with fibroblasts using a Transwell system. Radiation-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Western Blot analysis was conducted as previously described [ 49 ]. Primary antibodies, including p27 kip (ab62364), p16 INK4a (ab211542), Flotillin-1 (ab41927), CD81 (ab109201), Sirt2 (ab211033), and β-actin (ab179467), were purchased from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…Western Blot analysis was conducted as previously described [ 49 ]. Primary antibodies, including p27 kip (ab62364), p16 INK4a (ab211542), Flotillin-1 (ab41927), CD81 (ab109201), Sirt2 (ab211033), and β-actin (ab179467), were purchased from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxic mesenchymal stem cells, upon implantation, had a reversal on cardiac fibrosis via prevention of fibroblast to myofibroblast transition [34].…”
Section: Hypoxiamentioning
confidence: 99%
“…Other studies have shown that fibroblasts are targets of MSC, demonstrating an interplay between the two. Conditioned media from and cocultures with MSC have been shown to suppress the proliferation and myofibroblast differentiation of fibroblasts (155,157,160). Everything considered, while necessary and informative, in vitro work must always be taken with a grain of salt as not all culture conditions are physiologically relevant or reproducible in vivo, and culture conditions can even make a cancer cell appear phenotypically normal (152).…”
Section: Limitations and Current Needs In The Fieldmentioning
confidence: 99%